The Routledge companion to religion and popular culture - Lyden, John, 1959-; Mazur, Eric Michael (London ; New York : Routledge, 2015)
"Religion and popular culture is a fast-growing field that spans a variety of disciplines. This volume offers the first real survey of the field to date and provides a guide for the work of future scholars. It explores: key issues of definition and of methodology religious encounters with popular culture across media, material culture and space, ranging from videogames and social networks to cooking and kitsch, architecture and national monuments the representation of different religious traditions within the media and popular culture, mainly in the West but also including important non-western spheres such as Bollywood. Students will find the Companion an enjoyable and informative resource, whilst scholars will find it a stimulus to future work in the field"--
Introduction / John C. Lyden -- Part I: Approaching the discipline of religion and popular culture. Definitions : what is the subject matter of "religion and popular culture"? / John C. Lyden ; Conversations and confessions : who's writing about this, and why? / Eric Michael Mazur -- Part II: Encounters with popular culture. Section A: Mediated encounters. Introduction to Part II, Section A ; Television / Elijah Siegler ; Journalism / Jolyon P. Mitchell ; Film / John C. Lyden ; Radio / Tona Hangen ; Music / Mark Hulsether ; Video- and Internet games / Rachel Wagner ; Internet and social networking / Heidi A. Campbell and Paul Emerson Teusner ; Advertising / Tricia Sheffield -- Section B: Material encounters. Introduction to Part II, Section B ; Popular literature / Jennie Chapman ; Comics/graphic novels / Christine Hoff Kraemer and A. David Lewis ; Food and cooking / Benjamin E. Zeller ; Fashion / Edward Dutton ; Games and dolls / Nikki Bado and Rebecca Sachs Norris ; Kitsch / Leonard Norman Primiano -- Section C: Locative encounters. Introduction to Part II, Section C ; Shopping and consumption / Sarah McFarland Taylor ; Electronic dance music events / Graham St. John ; Sport / Jeffrey Scholes ; Monuments of civil religion / Darryl Caterine -- Part III: Religious traditions. Introduction to Part III ; Buddhism / James Mark Shields ; Roman Catholicism / Rodger M. Payne ; Hinduism / Sheila J. Nayar ; Islam / William Lafi Youmans ; Judaism / Eric Michael Mazur ; Mormonism / Lynita K. Newswander, Chad B. Newswander, and Lee Trepanier ; Contemporary paganism / Jodie Ann Vann ; Protestantism / Clive Marsh.
Includes bibliographical references and index.
Keywords: Popular culture -- Religious aspects; Religion and culture